Comparative Analysis of the Indian and Pakistani Nuclear Energy Development Programmes - A. A. Boyko (Сравнительная политика, 2015)
Due to the traditional competition between India and Pakistan, their strategic fields developing are interdependent. Nuclear power development programs are concerned as well. Pakistan falls behind India in this branch, however the specifics of the nuclear infrastructure let the potential of the states be relatively balanced. After Nuclear Suppliers Group granted a waiver to India in 2008 and Russia, France and USA, the new participants, broke into the market, India obtained an opportunity to make a breakthrough in the national nuclear program development, thus violating a status quo in fuel cycle technologies. Such chances stimulated China to violate the NSG guidelines and non-proliferations principles to get involved in Pakistani nuclear program development. The nuclear power Indian-Pakistani competition prospects largely depend on the Chinese position. Despite the international community suspects the Pakistani officials in nuclear black market dealing and the NSG guidelines China obviously supports the Pakistani nuclear field. This may result in preventing of escalation of tensions in the region.